2018
DOI: 10.1002/jmri.26312
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic R2* is more strongly associated with proton density fat fraction than histologic liver iron scores in patients with nonalcoholic fatty liver disease

Abstract: Background The liver R2* value is widely used as a measure of liver iron but may be confounded by the presence of hepatic steatosis and other covariates. Purpose To identify the most influential covariates for liver R2* values in patients with nonalcoholic fatty liver disease (NAFLD). Study Type Retrospective analysis of prospectively acquired data. Population Baseline data from 204 subjects enrolled in NAFLD/NASH (nonalcoholic steatohepatitis) treatment trials. Field Strength 1.5T and 3T; chemical‐shift encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 29 publications
7
29
4
1
Order By: Relevance
“…In many NAFLD patients, elevated ferritin may reflect a subclinical inflammatory state, rather than iron overload [31]. Similar to this observation, an R2* value on MRI (as an indicator of iron content) in its normal or minimally elevated range correlated more strongly with PDFF on MRI than the actual grade of hepatic iron content in patients with NAFLD [41]. Furthermore, low titers of autoimmune antibodies (in the absence of concomitant autoimmune hepatitis) are common and of no apparent clinical consequence [40].…”
Section: The Diagnosis and Evaluation Of Nafldsupporting
confidence: 54%
See 1 more Smart Citation
“…In many NAFLD patients, elevated ferritin may reflect a subclinical inflammatory state, rather than iron overload [31]. Similar to this observation, an R2* value on MRI (as an indicator of iron content) in its normal or minimally elevated range correlated more strongly with PDFF on MRI than the actual grade of hepatic iron content in patients with NAFLD [41]. Furthermore, low titers of autoimmune antibodies (in the absence of concomitant autoimmune hepatitis) are common and of no apparent clinical consequence [40].…”
Section: The Diagnosis and Evaluation Of Nafldsupporting
confidence: 54%
“…(A, B) T1-weighted magnetic resonance images showing the automatic capturing of the liver and (C) the summary of results that shows PDFF of the whole liver (13.2%) as well as R2* value (as a marker for liver iron content). R2* values of <126 S -1 are normal at 3T scanner examination[41].…”
mentioning
confidence: 87%
“…73 This means that any intervention that alters liver glycogen stores also can induce changes in T1 independent of inflammation and fibrosis. Another potential issue is the use of R2* for correction of T1 since there is a strong dependency of R2* on liver fat as shown recently by Bashir et al 74 In fact, in this study it was shown that liver fat is the most influential covariate of hepatic R2* both at 1.5 and 3T. This means that any intervention inducing a change in liver PDFF also will induce a change in cT1 owing to the change in R2*.…”
Section: O Ther Mr-based Biomarker For the Detec Tion Of Nafld An Dmentioning
confidence: 57%
“…Fibrosis, fat, and other hepatic cellular pathology contribute to R2 and R2* and interfere with liver iron content estimation [ 54 56 ]. The effect of fat has accuracy implications in NAFLD [ 55 ] but appears to be relatively small and may be minimised by mathematical correction [ 57 , 58 ]. In, addition, R2* can be obtained simultaneously with PDFF with Dixon-based sequences [ 55 , 56 , 59 ].…”
Section: Mpmri Methods In Clinical Practicementioning
confidence: 99%